Griscelli syndrome in skin of color: A trichoscopic perspective - Swapnil D Shah; Balachandra S Ankad; Sankappanavara V Smitha (Wolters Kluwer Medknow Publications, 2023)
Introduction: Griscelli syndrome (GS) is a very rare autosomal recessive disorder, belongs to group of "silvery hair syndromes" which includes Chediak-Higashi syndrome (CHS) and Elejalde syndrome. Hair light microscopy helps in the differentiation of GS and CHS, as both manifest with clinical features. Trichoscopy is useful in the diagnosis of many hair shaft disorders. Here, authors describe the trichoscopic features of GS in skin of color. Materials and Methods: This was an observational study conducted in a private dermatology clinic and in a tertiary care hospital. A total of 5 cases of suspected GS were referred by pediatrician. Consent was obtained. The demographic data in terms of age, gender, consanguinity, and clinical history was documented. Trichoscopic examination was performed with FotoFinder videodermoscope with 20× magnification, the clinical images were captured with Medicam 1000. Trichoscopy showed large and irregular pigment clumps in 4 cases. One case demonstrated hypopigmentation of hair without pigment clumps [Figure 3]a. Results: Trichoscopy showed large and irregular pigment clumps in 4 cases. One case demonstrated hypopigmentation of hair without pigment clumps. Conclusion: Trichoscopy shows characteristic features GS. It is a useful method when facility for light or polarized microscope is unavailable.